2019
DOI: 10.3390/ma12030459
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Current Instabilities in Conductive Atomic Force Microscopy

Abstract: Conductive atomic force microscopy (CAFM) is one of the most powerful techniques in studying the electrical properties of various materials at the nanoscale. However, understanding current fluctuations within one study (due to degradation of the probe tips) and from one study to another (due to the use of probe tips with different characteristics), are still two major problems that may drive CAFM researchers to extract wrong conclusions. In this manuscript, these two issues are statistically analyzed by collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…Again, this technique was chosen to prevent short currents from being measured. Voltages of 1, 2, 3, and 4 V were applied to the tip, and the resulting local current in the contact area of ∼100 nm 2 (ref ) was recorded simultaneously with the film topography (Figure S20). To estimate an upper value for the conductivity, only the highest positions within a scan were evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Again, this technique was chosen to prevent short currents from being measured. Voltages of 1, 2, 3, and 4 V were applied to the tip, and the resulting local current in the contact area of ∼100 nm 2 (ref ) was recorded simultaneously with the film topography (Figure S20). To estimate an upper value for the conductivity, only the highest positions within a scan were evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…The TUNA Current image (Figure 6b) is also showing a remarkably similar behavior (more bright contrast along the fiber direction). Since several factors influence the conductivity such as tip size and geometry, surface roughness, applied force between tip and sample, and formation of a thin water layer on the sample, [ 34 ] it is difficult to draw simple conclusions from these measurements. A more detailed estimation is therefore done by measuring I – V curves at different spots of the crystal.…”
Section: Resultsmentioning
confidence: 99%
“…7,[16][17][18][19] However, some of these studies showed that, for very small contacts ($50 nm or less), the expected current-contact area relationship does not always hold true. 16,17,20,21 One explanation for this lack of correlation is that trace contamination of the contact can inhibit conduction 22 such that the magnitude of the electrical current does not reect the size of the contact. 16,20 Certain environmental conditions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…16,17,20,21 One explanation for this lack of correlation is that trace contamination of the contact can inhibit conduction 22 such that the magnitude of the electrical current does not reect the size of the contact. 16,20 Certain environmental conditions (e.g. ambient conditions in which a water meniscus can form in the contact) can also break the correlation between current and contact area for nanoscale contacts.…”
Section: Introductionmentioning
confidence: 99%